Storm front [compact disc, unabridged] - Castle, Richard (Hyperion Audio, 2013)
Based on the hit ABC drama "Castle, " starring Nathan Fillion as crime writer Richard CastleNa character who is the bestselling author of the Nikki Heat and Derrick Storm mystery series.